Project-Based Learning for Student-Produced PSA on Mental Health and the SDGs - Supiarza, Hery; Tjahjodiningrat, Harry; Alfathadiningrat, Danendra (Bina Nusantara University, 2026)
Public Service Announcements (PSAs) represent a powerful medium for social communication, particularly in addressing complex issues such as mental health. However, limited research explores how students, as members of Generation Z, design PSAs within higher education frameworks that integrate global sustainability agendas. This study investigates how Project-Based Learning (PBL) enables students to conceptualize and produce PSAs on mental health in alignment with the Sustainable Development Goals (SDGs). Using a qualitative participatory approach combined with visual content analysis, this study examines 33 PSAs produced by Communication and Film students at Universitas Pendidikan Indonesia. The findings reveal distinct disciplinary orientations in PSA design. Communication students prioritize clarity and directness through textual and verbal strategies, whereas Film students emphasize symbolic depth and aesthetic experimentation. Two representative PSAs, Nomophobia and They Just Want to Be Heard, are analyzed in detail to illustrate these differences. The analysis highlights contrasts in narrative structure, cinematography, and sound design across disciplines. The results demonstrate that Communication students ensure accessibility, while Film students enhance emotional resonance, suggesting complementary strengths. Overall, the study contributes to communication research by linking narrative and audiovisual strategies with PSA effectiveness. It also contributes to education by illustrating the role of PBL in fostering collaboration and critical awareness among students. Additionally, the findings support SDG-related scholarship by demonstrating how student-produced media advances mental health literacy as part of sustainable development.